2024
DOI: 10.3389/fpsyt.2024.1328048
|View full text |Cite
|
Sign up to set email alerts
|

Depression and coronary heart disease: mechanisms, interventions, and treatments

Linjie Xu,
Xu Zhai,
Dazhuo Shi
et al.

Abstract: Coronary heart disease (CHD), a cardiovascular condition that poses a significant threat to human health and life, has imposed a substantial economic burden on the world. However, in contrast to conventional risk factors, depression emerges as a novel and independent risk factor for CHD. This condition impacts the onset and progression of CHD and elevates the risk of adverse cardiovascular prognostic events in those already affected by CHD. As a result, depression has garnered increasing global attention. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…A hyperfunction of the HPA axis can also alter cardiac autonomic function with sympathetic overactivation and parasympathetic hypofunction. This imbalance of the cardiac autonomic function may result in an increased heart rate, an increased myocardial contractility, and an increased myocardial oxygen consumption, which finally makes the heart more susceptible to malignant cardiac arrhythmias [ 11 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hyperfunction of the HPA axis can also alter cardiac autonomic function with sympathetic overactivation and parasympathetic hypofunction. This imbalance of the cardiac autonomic function may result in an increased heart rate, an increased myocardial contractility, and an increased myocardial oxygen consumption, which finally makes the heart more susceptible to malignant cardiac arrhythmias [ 11 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to compare the responses of the ANS in patients with MDD to challenges that stimulated the sympathetic and, respectively, the parasympathetic nervous systems. Due to the bidirectional relationship between MDD and CHD, given that MDD is a relevant risk factor for CHD and that patients with CHD and MDD often showed a more pronounced affection for the ANS than CHD patients without MDD [ 9 , 11 ], we focused on patients with MDD without known CHD.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted by Xu et al (2024) and Lin et al (2017) revealed the positive relationship between type D personality and increased depressive and anxiety symptoms among heart patients. In accordance with traditional risk factors, psychological factors have been shown as predictors of harmful heart disease outcomes.…”
Section: Introductionmentioning
confidence: 96%